Ketahanan Beberapa Genotipe Padi Hibrida (Oryza Sativa L.) Terhadap Pyricularia oryzae Cav. Penyebab Penyakit Blas Daun Padi. - Sheila Desi Kharisma; Abdul Cholil; Luqman i Qurata Aini (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
ABSTRACTThe objective of this research was to study the variance of hybrid ricegenotypes that showed resistance to leaf blast disease caused by Pyriculariaoryzae Cavara and got genotypes refined of the resistance . The research wasconducted at the Department of Disease Laboratory of Plant Pests and Diseases,Faculty of Agriculture, Univeristy of Brawijaya and in the P.T. DuPont’s researchfield in Ketawang Village, Bululawang, Malang since April until June 2012. Thisresearch used Randomized Block Design with 3 replications and 80 treatments.Eighty-treatments consisted of 24 restorer genotypes, 2 CMS genotypes, 24hybrid A genotypes, 24 hybrid B genotypes and 6 control genotypes (Maro,Hipa8, LP27P31, LP27P53, Ciherang and IR64). The results showed that therewere occurrence of intermediate resistance on 24 hybrid genotypes A and B.Twenty four hybrid A genotypes showed resistance reaction with moderateclassification which was equivalent to IR64 as the best control genotypes.Key word : Resistance, Leaf blas, Pyricularia oryzae Cavara